Development of Electronic Modules Integrated with PhET Simulation in Physics Subject XII Science Class - Amelia Dzikrina; Fetri Yeni J (Postgraduate, University of Mataram, 2024)
This research is motivated by the lack of visualization of abstract concepts, activation of students' senses and the number of damaged electrical kits in Physics causing low understanding of the material. This study aims to produce an E-Module that is valid, practical and effective. The type of research is research and development (R&D) with the ADDIE model. The research process includes analyze, design, development, implementation and evaluation. The sample of this research is XII science class students of SMAN 1 Kejuruan Muda. The data collection technique used was indirect communication technique. The data collection tool used a feasibility questionnaire on media, material and language aspects validated by three validators. Data analysis technique was done with qualitative description. Based on the results of data analysis, the average overall feasibility reached 88.00% (very feasible criteria), and the average practicality of teachers and students reached 96.00% (very practical criteria). The results of the data effectiveness test using one group pre test post test with a cognitive Ngain percentage of 81.39% and a psychomotor Ngain percentage of 76.39% with an effective interpretation. It can be concluded that the E-Module integrated with PhET Simulation can improve the results of concept understanding and students' science skills.